Cochlear Implant Receiver Location and Migration: Experimental Validation Pilot Study of a Clinically Applicable Screening Method - Markodimitraki, Laura M.; Stegeman, Inge; Smit, Adriana L.; Thomeer, Hans G. X. M. (Frontiers in Surgery, 2020)
Objectives: Postoperative follow-up after cochlear implantation lacks a reliable screening method to detect cochlear implant receiver device migration. This study aims to validate a clinically applicable method to assess the position and migration of the cochlear implant receiver device. Study design: Validation study. Setting: Tertiary university medical centre. Participants and method: To assess the cochlear implant receiver device location, round markers representing the external magnet were placed on both sides of the head of volunteers. Four independent clinicians took measurements of the distances between reference points on the head and the centre of the marker. The reference points were: the lateral canthus (LC), tragus tip (TT), the mastoid angle (MA) and the mandibular angle (AM). Main outcome measures: The inter-clinician reliability was determined by calculating the intraclass correlation coefficient (ICC) and confidence interval (CI) with a two-way mixed model and both consistency and absolute agreement types for each distance. Results: Eight volunteers were included resulting in 16 individual cases. The consistency type ICC’s for each reference point were: LC 0.90 (CI=0.80, 0.96), TT 0.83 (CI=0.69, 0.93), MA 0.75 (CI=0.56, 0.89) and AM 0.29 (CI=0.05, 0.59). The absolute agreement ICC’s were: LC 0.87 (CI=0.73, 0.95), TT 0.83 (CI=0.68, 0.93), MA 0.68 (CI=0.42, 0.86) and AM 0.18 (CI=0.01, 0.46). The inter-clinician reliability was good to excellent for the lateral canthus and tragus tip reference points. Conclusions: The cochlear receiver device location can be assessed reliably by measuring the distance between the LC, TT and the external magnet. This method can be used to registrate implant receiver location after implantation and detect implant migration postoperatively.